Neurophysiologic Mapping of Thalamocortical Tract in Asleep Craniotomies: Promising Results From an Early Experience. Issue 2 (2nd December 2020) - Simon, Mirela V; Lee, Daniel K; Choi, Bryan D; Talati, Pratik A; Yang, Jimmy C; Koch, Matthew J; Jones, Pamela S; Curry, William T
Abstract: BACKGROUND: Subcortical mapping of the corticospinal tract has been extensively used during craniotomies under general anesthesia to achieve maximal resection while avoiding postoperative motor deficits. To our knowledge, similar methods to map the thalamocortical tract (TCT) have not yet been developed. OBJECTIVE: To describe a neurophysiologic technique for TCT identification in 2 patients who underwent resection of frontoparietal lesions. METHODS: The central sulcus (CS) was identified using the somatosensory evoked potentials (SSEP) phase reversal technique. Furthermore, monitoring of the cortical postcentral N20 and precentral P22 potentials was performed during resection. Subcortical electrical stimulation in the resection cavity was done using the multipulse train (case #1) and Penfield (case #2) techniques. RESULTS: Subcortical stimulation within the postcentral gyrus (case #1) and in depth of the CS (case #2), resulted in a sudden drop in amplitudes in N20 (case #1) and P22 (case #2), respectively. In both patients, the potentials promptly recovered once the stimulation was stopped. These results led to redirection of the surgical plane with avoidance of damage of thalamocortical input to the primary somatosensory (case #1) and motor regions (case #2). At the end of the resection, there were no significant changes in the median SSEP. Both patients had no new long-term postoperative sensory or motor deficit. CONCLUSION: This method allows identification of TCT in craniotomies under general anesthesia. Such input is essential not only for preservation of sensory function but also for feedback modulation of motor activity.